Sthenelais limicola - Barnich, Ruth; Haaren, Ton Van (Zenodo, 2021)
Sthenelais limicola (Ehlers, 1864) (emended) Figs 1–2 Sigalion limicola Ehlers, 1864: 120. Sthenelais leiolepis Claparède, 1868: 406–409, pl. 4 fig. 3, pl. 6 fig. 1 (description sufficient; see also Barnich & Fiege 2003). Sthenelais haddoni McIntosh, 1897a: 403. Syn. nov. Sthenelais filamentosus Ditlevsen, 1917: 50, pl. 4 fig. 6, pl. 5 fig. 9. Syn. nov. ? Aphrodita arcta Dalyell, 1853: 170, pl. 24 fig. 14 (see McIntosh 1900; however, description insufficient). Sthenelais limicola – Pruvot & Racovitza 1895: 473, pl. 20 figs 122–123. — McIntosh 1900: 417, pl. 29 fig. 3, pl. 31 fig. 6, pl. 34 figs 9–11, pl. 42 figs 1–4. — Fauvel 1923: 113, fig. 42a–g. — Chambers 1985: 29–30, figs 1b, 2a, 15b–c, 21b–e. — Hartmann-Schröder 1996: 83 fig. 28. — Chambers & Muir 1997: 158, fig. 51. — Barnich & Fiege 2003: 132, fig. 65. — Gil 2011: 947. — Núñez et al. 2015: 244, fig. 98. Diagnosis Dorsal cirri absent on segment 3. Ventral body surface smooth. Outer elytral margin with irregular extensions (anterior elytra) or notched (posterior elytra); elytral surface smooth, except for some microtubercles near anterior margin. Parapodial stylodes smooth, slender, cirriform; notopodia with few long dorsal papillae; margins of anterior neuropodial bracts smooth. Notochaetae tapering to simple capillary tip. Type material (examined) The types of Sthenelais filamentosus were available for study: ICELAND • 5 syntypes; Northeast Atlantic, S Iceland, Medelland Bugt; 19 Jul. 1903; EtOH preserved; depth 70–90 fathoms (128–165 m); NHMD 658820. The type material of the following species is probably lost or was never deposited (type localities in brackets): Sigalion limicola (Croatia, Quarnero, Adriatic Sea), Sthenelais leiolepis (Italy, Gulf of Naples, W Mediterranean Sea) and Sthenelais haddoni (off SW Ireland, Northeast Atlantic). Other material (examined) UNITED KINGDOM • 2 specs; NW Irish Sea; stn CEFNWIS04 154a; 28 Jul. 2004; EtOH preserved; TUM 37563 (Figs 1B–C, 2) • 1 spec.; Irish Sea, Liverpool Bay; stn CEFSZ07 Z02a; 19 ...